Nei Endonuclease VIII-Like1 (NEIL1) Inhibits Apoptosis of Human Colorectal Cancer Cells. (27th June 2020) - Xue, Wanjuan; Liu, Yongcheng; Xin, Ningning; Miao, Jiyu; Du, Juan; Wang, Yu; Shi, Haiyan; Wei, Yameng; Zhang, Huahua; Chen, Yani; Gao, Yi; Li, Dan; et al.
Abstract : The study is aimed at investigating the role of Nei endonuclease VIII-like1 (NEIL1) in the pathogenesis of colorectal cancer (CRC). The human CRC (HCT116 and SW480) cells were subjected to the siRNA silencing and recombinant plasmid overexpression of NEIL1. Transfection of siNEIL1 significantly inhibited the cell growth. It also increased the Bax expression levels, while it decreased the Bcl-2 expression levels in human CRC cells, leading the Bax/Bcl-2 balance toward apoptosis. Moreover, the apoptosis was promoted through the caspase-9 signaling pathway. One the other hand, high expression of NEIL1 promoted the cell viability and reduced the apoptosis, inducing the balance of Bax/Bcl-2 in the human colon cancer cells to be antiapoptotic. In addition, the caspase-9 signaling pathway inhibited apoptosis, contrary to the results obtained by downregulating NEIL1 expression. Furthermore, NEIL1 was negatively regulated by miR-7-5p, indicating that miR-7-5p inhibited the NEIL1 expression after transcription. Overexpression of miR-7-5p reversed the effects of NEIL1 on these CRC cells. In conclusion, NEIL1 promotes the proliferation of CRC cells, which is regulated negatively by miR-7-5p. These findings suggest that NEIL1 is a potential therapeutic target for CRC.